Prime submodul of an integer over itself - Muhammad Rijal Alfian; Fariz Maulana; Ni Wayan Switrayni; Qurratul Aini; Dwi Noorma Putri; I Gede Adhitya Wisnu Wardhana (University of Mataram, 2022)
One of the sciences used in digital security systems is cryptography. Cryptography is closely related to the integer system, especially prime numbers. Prime numbers themselves have been abstracted a lot. One form of abstraction of prime numbers is the prime ideal. Previous studies have proven that an Ideal is said to be a prime ideal on if and only if I is constructed by a prime element. Other studies have also shown how the prime ideal develops. One of them is the research result of Dauns, where the prime ideal form is developed in the form of a prime submodule. A prime submodule is one of the objects in the module, which is an abstraction of prime numbers. Based on these things, it is exciting if the properties of the prime submodule are applied to other module forms, one of which is the integer module.